Insecticide-treated nets utilization and influencing factors on middle school students in Southeast Nigeria. A cross-sectional study - Egbobe JohnPaul Otuomasiri; Magnus Michael Sichalwe; Ezaka Ephraim Ibeabuchi (Clinical Epidemiology and Global Health)
Background: Malaria is a major cause of mortality, leading to higher healthcare costs and reduced household income, particularly among low-income individuals. Successful eradication relied on individual acceptance, participation, and continuous education about control measures. This study explored factors influencing insecticide-treated net (ITN) utilization among middle school students in Southeast Nigeria. Methods: An analytical cross-sectional study was conducted from October to November 2020, using systematic sampling to recruit 238 participants from three schools in Southeastern Nigeria. Data were analyzed with SPSS version 23, employing descriptive statistics for univariate analysis to determine ITN usage proportions. Bivariate analysis utilized cross-tabulation, while multivariate analysis involved linear regression. Results: Most (96.6 %) were aware of ITNs, but regular usage was low at 20.6 %. Knowledge of ITNs and parental employment significantly influenced usage, with employed parents and greater awareness linked to higher utilization. Participants aged 15–19 were 2.258 times more likely to use ITNs than those aged 20–24. Additionally, awareness of ITNs increased the likelihood of usage by 8.638 times, and each point increase in malaria risk perception correlated with a 30.2 % increase in ITN usage likelihood. Conclusion: Despite widespread awareness of ITNs, regular use is low, especially among students aged 20–24 and unemployed households. The positive link between knowledge and ITN use highlights the need for effective health education. Additionally, free distribution significantly boosts consumption, underscoring the importance of tailored interventions for vulnerable populations. Enhancing community understanding and access to ITNs is crucial for improving malaria prevention efforts.